2012
DOI: 10.1097/anc.0b013e318265b299
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Experiences Expressing Breast Milk for Their Preterm Infants

Abstract: Individual mother's needs for privacy need to be determined and interventions to support mothers' feeding plans throughout hospitalization and at discharge need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…A recent quantitative study 41 reported that the majority of mothers preferred pumping at home, however, some of the mothers interviewed for the current study preferred pumping at the hospital. A recent quantitative study 41 reported that the majority of mothers preferred pumping at home, however, some of the mothers interviewed for the current study preferred pumping at the hospital.…”
Section: Discussionmentioning
confidence: 58%
“…A recent quantitative study 41 reported that the majority of mothers preferred pumping at home, however, some of the mothers interviewed for the current study preferred pumping at the hospital. A recent quantitative study 41 reported that the majority of mothers preferred pumping at home, however, some of the mothers interviewed for the current study preferred pumping at the hospital.…”
Section: Discussionmentioning
confidence: 58%
“…The facilitators and barriers to initiation of lactation/pumping and maintenance of milk supply within the context of an infant hospitalized in the NICU are numerous. However, the majority of literature available on this topic is restricted to the term and preterm infant population and the samples often exclude any infant born with a congenital anomaly (Alves, Rodrigues, Fraga, Barros, & Silva, ; Dowling, Blatz, & Graham, ; Rossman, Kratovil, Greene, Engstrom, & Meier, ). For mothers of infants with CDH, some of factors are similar whereas others are specific to this population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show the importance of ‘privacy’, in neonatal care [13] as well as during breastfeeding [24,38]. However, the need for parental privacy may be in tension with percieved health professional imperatives to maintain surveillance of the patient, in this case the baby described by Johnson et al [39], as an aspect of professional power.…”
Section: Discussionmentioning
confidence: 99%